Parents’ Growth Mindsets and Home-Learning Activities: A Cross-Cultural Comparison of Danish and US Parents - Justice, Laura M.; Purtell, Kelly M.; Bleses, Dorthe; Cho, Sugene (Frontiers in Psychology, 2020)
Mindset is a term commonly used to represent an individual’s beliefs about the role of ability and effort in learning. In this study, we assessed parental mindset – ability mindset and effort mindset – for 497 parents in two countries (U.S. and Denmark), all of whom had at least one child between 3 and 5 years of age. Of primary interest was assessing the relations between parental mindset and home-learning activities of four types: family learning activities, learning extensions, parental time investment, and parental school involvement. Findings showed that parents in the U.S. and Denmark held similar ability and effort mindsets, but differed significantly in home-learning activities, with U.S. parents providing significantly more family learning activities, learning externsions, and parental time investment than Danish parents, although the latter had significantly higher levels of school investment. Further, findings showed that parents’ effort mindset was a significant predictor of family learning activities and parental time investment, and that country moderated the relations between effort mindset and parental time investment. For U.S. parents, higher levels of effort mindset were associated with higher levels of parental time investment, but this was not the case for Danish parents. We call for experimental work to determine the causal relations between parental mindset and home-learning activities, and rigorous cross-cultural research to explore the universality of parental mindset in distinctive cultural settings.